The relationships between nurse care, attitude of patient and nurse with cancer patient satisfaction - Abdalla Musbah, Fadia (2015)
This study investigates the relationships between nurse care, attitude of patient and nurse with cancer patient satisfaction using the quantitative methodology. In Libya, the challenge of medical facilities and treatment is a current issue. Thus, this study was conducted to investigate the patients’ satisfaction at National Cancer Institute Misurata, Libya. The participants were 217 cancer patients of National Institute of Oncology located in Misurata, Libya. The study scale was adopted and adapted from that used by previous researchers to measure nurse care, nurse attitude, patient attitude, hospital service quality and patient satisfaction on a 5-point Likert scale. The nurse care, nurse attitude and patient attitude are independent variables and cancer patient satisfaction is the dependent variable in this study. On the other hand, hospital service quality and patient characteristic are control variables. SPSS software was used to analyses the data collected. The analyses of this study included descriptive statistic, correlation analysis and multiple regression analysis. The study found that on the overall basis, there is a significant statistical relationship between nurse care and cancer patient satisfaction, and there is a significant statistical relationship between attitude and cancer patient satisfaction. The sub-hypotheses show that there are no a relationship between interpersonal skills of nurse care and efficiency of nurse care with cancer patient satisfaction which suggest there might be interactions between these variables. Result also shows that for the sub-hypotheses, only patient attitude and cancer patient satisfaction indicated significant relationship, while there is no significant relationship between nurse attitude and patient satisfaction. This also indicates of possible interactions between the variables. On an overall basis, it can be concluded that to increase in the satisfaction level cancer patient, the management do it by focusing on improving the level of nurse care, nurse attitude and patient attitude.